Analisis Perilaku Bullying dan Upaya Penanganannya pada MIS Terpadu Langsa - suhelayanti suhela; Elma Zahradafia; Syamsiah Syamsiah (Prodi Bimbingan dan Konseling Islam, 2023)
The purpose of this study was to find out and analyze how bullying behavior in students and efforts to handle bullying behavior in Langsa Integrated MIS. The research method used is descriptive analytic qualitative method. Data collection techniques used are observation, in-depth interviews and documentation. Data analysis techniques in this study include data reduction, data presentation and drawing conclusions. By way of narrative analysis: this technique involves collecting and analyzing data in the form of stories or narratives from individuals who have experienced bullying or were involved in efforts to deal with it, to understand the experiences and perspectives of informants. The results of the study are that there is bullying behavior of students at Langsa Integrated MIS, the form of the behavior is in the form of physical, verbal, psychosocial and social media. Physically, the forms of bullying include hitting, tripping, pinching, kicking, refusing, taking and breaking things. The forms of verbal bullying include mocking/calling friends names with certain nicknames (name calling), calling parents names, and yelling or compromising (asking for something by force). Psychologically by isolating, and finally cyber bullying by humiliating. The intensity of bullying at the Integrated MIS is slow when viewed in terms of its frequency, there are acts of bullying carried out by students every day and there are at least 1-2 cases. Meanwhile, when viewed from the quality, the bullying that occurs in general can be said from mild bullying to moderate bullying. This can be seen from the impact that only a few felt sick, the rest cried and felt scared after the bullying. The handling efforts that have been carried out at the Langsa Integrated MIS include coaching and supervision, such as advising and monitoring student activities during free hours or outside the classroom so that bullying behavior does not repeat itself.